2019
DOI: 10.1016/j.ymthe.2019.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Glioma Cell-Secreted Exosomal miR-301a Activates Wnt/β-catenin Signaling and Promotes Radiation Resistance by Targeting TCEAL7

Abstract: Recent evidence suggests that microRNAs (miRNAs) can be released to the extracellular microenvironment and mediate cell-cell communication through exosomes. The aim of this study was to identify exosomal miR-301a (exo-miR-301a) involved in glioblastoma (GBM) radioresistance and reveal the possible mechanisms. The exo-miR-301a specifically secreted by hypoxic GBM cells could transfer to corresponding normoxia-cultured cells and promote radiation resistance. Hypoxic exo-miR-301a directly targeted TCEAL7 genes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 27 publications
(32 reference statements)
1
114
0
Order By: Relevance
“…Moreover, silencing of TCEAL7 was revealed to promote the expression of Cylin D1 and in the end promotes non-small cell lung cancer progression [18] . Another work indicated TCEAL7 could be regulated by miR-301a to regulate glioma cell radiation resistance [19] . In GC, TCEAL7 was revealed to be decreased expression and correlated with prognosis of cancer patients [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, silencing of TCEAL7 was revealed to promote the expression of Cylin D1 and in the end promotes non-small cell lung cancer progression [18] . Another work indicated TCEAL7 could be regulated by miR-301a to regulate glioma cell radiation resistance [19] . In GC, TCEAL7 was revealed to be decreased expression and correlated with prognosis of cancer patients [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal ncRNAs released by glioma cells can also interfere with the sensitivity to radiotherapy and thus affect the treatment efficiency. Yang et al reported that exosomal miR-301a specifically secreted by hypoxic GBM cells could transfer to corresponding normoxiacultured cells and promote radiation resistance by targeting TCEAL7 genes [79]. In addition, a recent study demonstrated that circRNA-ATP8B4 from radioresistant GBM derived EVs could also promote glioma radioresistance by sponging miR-766 [78].…”
Section: Exosomal Ncrnas and Treatment Resistancementioning
confidence: 99%
“…In contrast, miR-301a-mediated TCEAL7 inhibition increased transcriptional activity of β-catenin. Moreover, inhibition of miR-301a and overexpression of TCEAL7 reversed the radioresistant miR-301a phenotype in GMB cells in vitro and in vivo [93]. These opposite effects could be attributed to a cell-line specific miR-301a function.…”
Section: Mirnasmentioning
confidence: 92%
“…Contradictory effects of miR-301a on Wnt/β-catenin signaling pathway and radiosensitivity were demonstrated. miR-301a was shown to directly target Wnt that activates and TCEAL7 that suppress β-catenin signaling [58,93]. Upregulation of miR-301a directly inhibited Wnt and indirectly β-catenin and cyclin D1 in ESCC cells and this led to increased radiosensitivity, reduced proliferation and migration of ESCC cells [58].…”
Section: Mirnasmentioning
confidence: 99%